Analysis of Hybrid Learning Model Interest Selection for students using the Multi-Attribute Utility Theory Method Case Study: Mulia University - Wahyu Nur Alimyaningtias; Risdin Saputra; Ari Prayogo; Tri Sudinugraha (Brilliance: Research of Artificial Intelligence, 2023)
Hybrid learning is a learning method that combines or combines online learning with face-to-face learning (PTM). so that in its implementation, there are times when students and teaching staff meet face to face in class. However, in its implementation there are several obstacles, one of which is the number of students attending class and decreasing interest in learning, resulting in a poor final semester assessment. In connection with the problems faced, this research will try to measure interest in the hybrid learning model that has been implemented at Mulia University using the Multi-Attribute Utility Theory method, where this method is a decision-making method used to evaluate alternatives by considering several attributes. relevant and selecting the alternative that best meets the needs and preferences of the decision maker.